Hubungan Antara Self-Efficacy dengan Academic Buoyancy pada Mahasiswa di Kota Bekasi - Farah Syaufika; Yulia Fitriani; Fathana Gina (INDO PUBLISHING, 2026)
This study aimed to examine the relationship between self-efficacy and academic buoyancy among university students in Kota Bekasi. Academic buoyancy refers to students' ability to cope with everyday academic challenges, while self-efficacy refers to an individual's belief in their capacity to execute actions to achieve specific goals. This study employed a quantitative correlational approach. A total of 115 active undergraduate students enrolled at universities in Kota Bekasi, taking regular classes, in semester 4, 6, or 8, and enrolled in a minimum of 20 credit units were recruited through incidental sampling using the Lemeshow formula. The instruments used were a self-efficacy scale adapted from Darmayanti et al. with 22 valid items (α = .816) and an academic buoyancy scale developed by the researcher based on Martin and Marsh's theory with 14 valid items (α = .734). Data were analyzed using Spearman Rank Order correlation due to non-normal data distribution. The results revealed a significant positive relationship between self-efficacy and academic buoyancy with a strong correlation strength (rho = .695, p < .001). The findings show that self-efficacy and academic buoyancy have a strong positive relationship. It is recommended that students need to build confidence in managing academic demands, while universities should provide programs designed to enhance self-efficacy (for example, thru academic mentoring and counseling).